Effectiveness of intra-cardiac lidocaine and intra-amniotic digoxin at inducing fetal demise before second trimester abortion past 20 weeks at a tertiary Hospital in Ethiopia: A retrospective review - Abraham Fessehaye Sium; Tesfaye H. Tufa; Jaclyn M. Grentzer; Sarah Prager (Elsevier, 2022)
Background: Current literature recommends inducing fetal demise prior to second trimester medication abortion beyond 20 weeks of gestation. There is inadequate literature regarding the practice and effectiveness of this procedure in low-income countries. This study aimed at documenting the effectiveness of intra-cardiac lidocaine and intra-amniotic digoxin at inducing fetal demise before second trimester medication abortion in an Ethiopian setting. Methods: This is a retrospective chart review conducted at St. Paul's Hospital Millennium Medical College, in Ethiopia. A total of 65 cases of feticide administration before 2nd trimester medication abortion between 20 and 28 weeks of gestation (From April 1, 2021 to September 30, 2021) were reviewed. The primary outcome was cessation of fetal cardiac activity the day after the first feticide injection. Data were extracted by reviewing maternal charts using a data extraction tool prepared in English. Data were analyzed using SPSS version 23. Simple descriptive statistics were used to analyze baseline characteristics and fetal demise outcomes. Results were presented in percentages and frequencies. Results: More than three quarters of the feticide injections were with intra-amniotic digoxin, while the rest (24.6%, 16/65) were with intra-cardiac lidocaine. Injection of digoxin or lidocaine was effective at inducing fetal demise the day after administration in 92.3% (60/65) of the cases. Intracardiac lidocaine administration was 100% (16/16) effective at inducing fetal demise within the day after the injection while the effectiveness of digoxin within the same period was 89.8%. Conclusion: In this study, both intra-amniotic digoxin and intra-cardiac lidocaine were effective at inducing fetal demise, which is in support of findings from similar previous studies. Implications: In an Ethiopian setting, both intra-amniotic digoxin and intra-cardiac lidocaine injections are effective at inducing fetal demise before second trimester abortion beyond 20 weeks of gestation within the next day after feticide administration.